SOCIALLY DEMOGRAPHIC PORTRAIT OF A HAPPY AND UNHAPPY RESIDENT OF LATGALE - Kalvāns, Ēriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this scientific research article is the presentation of socio-demographic portraits of the happy and unhappy Latgale inhabitants.A key concept of “happiness” is used in this publication. The theoretical interpretation of the happiness phenomenon is based on the findings of positive psychology, according to which happiness is defined as a life satisfaction and positive evaluation of his life and positive emotions over negative emotions.As the research field Latgale region has been chosen because this is the region of Latvia with the lowest socio-economic development, which is considered one of the poorest regions in the European Union - so it acquires a special topicality of problem of happiness and its socially demographic aspects.“Oxford happiness questionnaire”(Hills & Argyle, 2002) adapted by the author to Latvian culture and socio-demographic survey (Kalvāns, 2013), were used in the research paper. As a result of the research a general socio-demographic portrait of a Latgalian resident was created depending on the structure of happiness.